Rapeseed meal nutraceuticals (Journal of Oilseed Brassica, 2026)
Many components of human diet previously overlooked are now considered to play an important role in the prevention and treatment of important diseases. Over the last decade disease preventing food and ingredients (called nutraceuticals) have written some success stories. Today the most important nutraceutical formulations contain vitamins, with antioxidant properties, oligosaccharides, bioactive peptides, phenolic compounds, glucosinolates and other products. Studies showed that cruciferous seed meals that include rapeseed exerted protective effects against tumour formation and growth. Rapeseed is reported to have a broad range of therapeutic effects, including antioxidant, anti-inflammatory, antitumour and anticancer effect. The medicinal properties of rapeseed are due to presence of variety of phytochemicals imparting the effect. In the laboratory, rapeseeds have been found to have very strong antioxidant activity, inhibiting cancer cell proliferation, decreasing lipid oxidation, and lowering cholesterol. While extensive research have been done, a literature review for health benefits of rapeseed meal and their phytochemicals has not been compiled to summarize the investigations to provide a baseline for considering rapeseed meal in isolating nutraceuticals and developing functional food. This review attempts to report the medicinal properties of individual bioactive component, with the recent updates in vivo and in vitro research to explore the possibility of utilizing rapeseed meal in development of functional food. The consideration of all the bioactive components of rapeseed meal is beyond the purview of this review. Hence, only extensively studied major bioactive components viz. rapeseed phenolics, glucosinolates, dithiolthiones, phytates, phytosterols and bioactive peptides are considered.